2014
DOI: 10.1111/ppa.12309
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the genetic diversity and evolution of Little cherry virus 1

Abstract: Little cherry virus 1 (LChV-1), a member of the recently proposed genus Velarivirus, is a sweet cherry pathogen that has been recently reported to infect other Prunus species and is associated with various plant disorders. In this work the incidence of the virus on its putative hosts and possible mechanisms driving its evolution were investigated. Due to problems encountered with LChV-1 detection, a new nested RT-PCR assay was developed and applied. The virus was found to be prevalent in cherry plantations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 23 publications
6
21
0
Order By: Relevance
“…Recombination is a powerful evolutionary driving force that results in the generation of new genotypes in RNA viruses [85,86]. Recombination events have been previously reported in RNA viruses in the family Betaflexiviridae and Closteroviridae [79,84,87,88] and in this study, multiple recombination events were identified amongst Australian isolates of ACLSV, CGRMV, CVA, LChV1, LChV2 and PBNSPaV. All the Australian recombinant isolates shared similar phylogenetic groupings with their major parental sequence which indicates close genetic connectivity within the population of these recombinants.…”
Section: Discussionmentioning
confidence: 98%
“…Recombination is a powerful evolutionary driving force that results in the generation of new genotypes in RNA viruses [85,86]. Recombination events have been previously reported in RNA viruses in the family Betaflexiviridae and Closteroviridae [79,84,87,88] and in this study, multiple recombination events were identified amongst Australian isolates of ACLSV, CGRMV, CVA, LChV1, LChV2 and PBNSPaV. All the Australian recombinant isolates shared similar phylogenetic groupings with their major parental sequence which indicates close genetic connectivity within the population of these recombinants.…”
Section: Discussionmentioning
confidence: 98%
“…A third group is formed with the isolates Jerte, Ponferrada, Taian and YD [ 5 , 6 , 7 ]. Phylogenetic analyses using partial sequences of the RdRp, the HSP70h and the CP have classified LChV1 isolates into 4 clusters, including the three above mentioned ones [ 8 ]. Even though the intragroup diversity appears to be relatively low (3.3% to 7.4% in nts), the genetic distances between the different phylogenetic groups are higher (15% to 39% in nts) [ 3 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, seven novel LChV1 isolates were fully sequenced using HTS technologies. One of the isolates (G15 3) was recently partially characterized and shown to exhibit the highest genetic divergence from all so far known isolates [ 8 ]. The sequences of the other LChV1 isolates described herein were acquired during HTS analysis of several sweet or flowering cherry samples from three different countries.…”
Section: Introductionmentioning
confidence: 99%
“…Infection of cherry by LChV-1 has been reported all over the world [ 37 , 38 , 39 , 40 ], usually as a coinfection with CVA. Moreover, its presence was also reported from different hosts (almond, peach and plum) [ 35 , 41 ] and recently from apricot [ 17 ]. It is graft-transmittable and although its close relative LChV-2 is transmitted by mealybugs, LChV-1 still lacks a confirmed vector.…”
Section: Introductionmentioning
confidence: 77%
“…It is graft-transmittable and although its close relative LChV-2 is transmitted by mealybugs, LChV-1 still lacks a confirmed vector. Its positive sense RNA genome has eight ORFs, including ORF3 encoding a heat-shock protein 70 homologue (HSP70h) and ORF5 and ORF6 encoding two coat proteins [ 41 ].…”
Section: Introductionmentioning
confidence: 99%